Demonstration of a Mobile Education Artifact in a Tanzania’s Higher Education Institution - Mwandosya, Godfrey Isaac; Suero Montero, Calkin; Mbise, Esther Rossiner; Oyelere, Solomon Sunday (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study reports the demonstration of the effectiveness of a mobile education tool (MET) that was co-designed and developed at the College of Business Education (CBE) in Tanzania by a team of teachers, researchers, and a developer using the Design Science Research (DSR) methodology. The demonstration of the CBEMET Prototype as an artifact was done to 30 teachers who had participated in the co-designing of the prototype phase, 3 members of CBE management team and 20 students in Bachelor II degree program as the observers and representative of those who will use the prototype at a later stage. Different sets of questionnaires were administered to the teachers, the members of the management team and the students. The demonstration confirmed that it is easy to access the prototype, share learning contents, and provide education through mobile devices. Nonetheless, teaching materials prepared for testing the prototype were insufficient and thus needed improvement. Furthermore, teachers and observers proposed for more options to the prototype such as the inclusion of timetables, alerts of events like examination dates, and news on innovation activities. The feedback from the participants has thus been considered to reduce errors in the usage of the prototype before its final deployment.